Penguatan Karakter BAKU di Era Masyarakat 5.0 Pada Siswa SMK Daarut Tauhid - Mubarok, Agus; Azhim, Faiha Athiyah; Ramadhani, Hana Thufailah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
The world is entering the era of society 5.0. some skills such as innovation, creativity, and collaboration are needed to be a solution to every problem of this era. Strengthening character is an important thing to prepare for the